Workforce Diversity, Diversity Hiring, and Inclusion Training: The Mediating Role of Employee Perceptions in Manufacturing Company - Diah Ayu Syahrani Putri; Cindy Apriyanih (DEAL: International Journal of Economics and Business, 2025)
This study examines the influence of Diversity Hiring Practices and Inclusion Training Programs on Workforce Diversity , mediated by Employee Perception of Inclusion, in manufacturing companies in the East Jakarta Industrial Park (EJIP) area. In the Industry 4.0 era, workforce diversity is a strategic factor that can drive innovation and organizational performance. This study uses a quantitative approach with data collection through questionnaires on 141 respondents selected by purposive sampling. The research variables were measured using a 5-point Likert scale, and data analysis was conducted with SmartPLS. The results of the study indicate that Diversity Hiring Practices and Inclusion Training Programs do not have a significant direct effect on Workforce Diversity. However, through Employee Perception of Inclusion as a mediating variable, both provide a significant positive contribution to workforce diversity. Employee perceptions of inclusivity have been shown to be a strategic mechanism that transforms diversity initiatives into substantial results. This highlights the theoretical novelty of the research, where signal theory is applied earlier in the analysis to explain how diversity-related signals shape employee inclusion perceptions and translate into organizational outcomes. Furthermore, this study highlights that the success of diversity initiatives requires a holistic approach that encompasses the development of an inclusive organizational culture, employee retention, and a comprehensive training strategy. This study provides theoretical contributions through the integration of signal theory in a manufacturing context, explaining how organizational signals influence employee perceptions and behaviors. Practically, these results provide a foundation for organizations to design more effective diversity strategies, including the implementation of experience-based training and inclusive leadership development. The implications of this research encourage further exploration of workforce diversity management strategies, particularly in highly structured industrial environments.